Development of core competencies for field veterinary epidemiology training programs - Pinto, Julio; Dissanayake, Ravi Bandara; Dhand, Navneet; Rojo-Gimeno, Cristina; Falzon, Laura Cristina; Akwar, Holy; Alambeji, Rianatou Bada; Beltran-Alcrudo, Daniel; Castellan, David Mario; Chanachai, Karoon; Guitian, Javier; Hilmers, Angela; et al. (Frontiers in Veterinary Science, 2023)
A workforce with the adequate field epidemiology knowledge, skills and abilities is the foundation of a strong and effective animal health system. Field epidemiology training is conducted in several countries to meet the increased global demand for such a workforce. However, core competencies for field veterinary epidemiology have not been identified and agreed upon globally, leading to the development of different training curricula. Having a set of agreed core competencies can harmonise field veterinary epidemiology training. The Food and Agriculture Organization of the United Nations (FAO) initiated a collective, iterative, and participative process to achieve this and organised two expert consultative workshops in 2018 to develop core competencies for field veterinary epidemiology at the frontline and intermediate levels. Based on these expert discussions, 13 competencies were identified for the frontline and intermediate levels. These competencies were organised into three domains: epidemiological surveillance and studies; field investigation, preparedness and response; and One Health, communication, ethics and professionalism. These competencies can be used to facilitate the development of field epidemiology training curricula for veterinarians, adapted to country training needs, or customised for training other close disciplines. The competencies can also be useful for mentors and employers to monitor and evaluate the progress of their mentees, or to guide the selection process during the recruitment of new staff.